Making a difference : strategic communications to end violence aganist women (UNIFEM New YorkUS, 2003)
Offers practical advice, stories and lessons learned by women and men all over the world working to end violence against women as well as overviews of communications processes.
Keywords: VIOLENCE AGAINST WOMEN